Challenges and Opportunities for in situ Maintenance of the Native Brazilian Cotton Gossypium mustelinum Miers - Barroso, Paulo Augusto Vianna; Hoffmann, Lúcia Vieira; da Costa, Nataly Duarte Lopes (Frontiers in Ecology and Evolution, 2021)
The native Brazilian cotton Gossypium mustelinum has never been planted. It is tetraploid and may cross with cultivated cotton. Endemic to Northeast Brazil, it was known only to grow in semi-arid areas, but expeditions in 2011, 2016, and 2018 localized plants in preservation areas on the coast of Northeast Brazil (in the States of Paraiba and Pernambuco), as predicted before by niche simulations. New climatic modeling shows that new populations can still be found in the Pernambuco semi-arid area, despite the lack of herbarium and germplasm bank information. Historical data show that the preserved populations are in regions where sympatry has not occurred in the last 47 years. Gene flow is unlikely to be a threat, and communication may foster significantly in in situ preservation.